KAIDAH BAHASA DALAM MENAFSIRKAN AL-QUR'AN - Sukron Jamil; Alwizar (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2025)
Abstract The interpretation of the Al-Qur'an is a scientific endeavor that requires a profound mastery of Arabic linguistic rules to accurately comprehend the messages of revelation. This study explores the linguistic principles underlying Al-Qur'an interpretation, including the use of pronouns (isim dhamir), the distinction between definite (ma’rifah) and indefinite (nakirah) nouns, singular (mufrad) and plural (jama’) forms, and the concept of synonyms that are often misunderstood. The research discusses the importance of understanding nouns (isim) and verbs (fi’il) in terms of time, attributes, and meaning. A qualitative descriptive approach is employed to analyze data from Al-Qur'an verses and tafsir literature. The findings reveal that mastery of linguistic principles not only enhances the accuracy of interpretation but also ensures the relevance of the Al-Qur'an message in modern contexts. This study makes a significant contribution to the development of Al-Qur'an exegesis, particularly in fostering a comprehensive and structured hermeneutics of the Al-Qur'an.